5510 sayılı kanuna göre Sosyal Güvenlik Kurumunun üçüncü kişilere rücuu - Kovancı, Nuray (My University, 2022)
Hukukumuzda, Sosyal Güvenlik Kurumu sosyal riskin gerçekleşmesi ile birlikte sigortalıya veya sigortalının ölümü hâlinde hak sahiplerine gerekli yardımları yapmakla yükümlü kılınmıştır. Bununla birlikte Kuruma, sigortalı veya hak sahipleri için yaptığı gider ve ödemeler ile sigortalı veya hak sahiplerine bağladığı gelir ve aylıkları zarar veren sigorta olayının gerçekleşmesinde sorumlu bulunan üçüncü kişilerden talep etme hakkı tanınmıştır. 5510 sayılı Sosyal Sigortalar ve Genel Sağlık Sigortası Kanunu’nun 21/ 4., 39. ve 76/ 6. maddelerinde Kurumun üçüncü kişilere rücu hakkı düzenlenmiştir. Üçüncü kişiler, kısa vadeli sigorta kolları bakımından iş kazası ve meslek hastalığı ile hastalık sigortası (m. 21/ 4); uzun vadeli sigorta kolları bakımından malullük ve ölüm sigortası (m. 39) ile genel sağlık sigortası (m. 76/ 6) kapsamında Kuruma karşı sorumlu tutulmuştur. Kurum üçüncü kişilere rücu hakkını ancak Kanunda belirtilen hâllerde kullanabilir. Rücu hakkının konusu Kanunda belirtilen sosyal sigorta yardımları ile sınırlıdır.

In our legislation, the Social Security Institution are obliged to provide necessary benefits to the insurance holders or the right holders, in case of the death of the insurance holders, with the realization of the social risk. In addition, the Institution is entitled to request the expenses and payments, made to the insurance holders or the right holders, and the incomes and salaries, allowed to the insurance holders or the right holders, from the third parties, who are held responsible from the damaging insurance incident. Within the provisions of the Articles 21/ 4, 39 and 76/ 6 of the Law No. 5510 on Social Insurance and General Health Insurance, the right of recourse of the Institution against the third parties are enacted. The third parties are held responsible to the Institution within the scope of work accident, occupational disease and health insurance in terms of the short-term insurance branches (Article 21/ 4); invalidity and survivors’ insurance in terms of the long-term insurance branches (Article 39) and general health insurance (Article 76/ 6).The Institution may only use the right of recourse against the third parties under the conditions, prescribed in the Law. The subject of right of recourse is limited with social insurance assistance, listed in the Law.
The recourse of the Social Security Institution against third parties in accordance with the Law No. 5510
Keywords: 5510 Sayılı Kanun; halefiyet; Law and legislation; right of recourse; rücu hakkı; Social security; Social Security Institution; Sosyal güvenlik; Sosyal Güvenlik Kurumu; Sosyal Güvenlik Kurumu (Turkey); Sosyal Güvenlik Kurumu (Türkiye); subrogation; the Law No. 5510; third party; Turkey; Türkiye; üçüncü kişi; Yasa ve yasama